What a feeling?: the role of emotion processing and social cognition in patients with medically unexplained symptoms - Erkic, Maja (2021)
Patients with MUS are not only characterized by experiencing distressing somatic symptoms and health related abnormal thoughts, feelings and behaviours, but also by difficulties understanding and expressing own feelings, reflected by high levels of alexithymia. Moreover, alexithymia has been linked to poor emotion regulation and more specifically to expressive suppression of emotions, which in turn has been associated with social distress and less positive social interactions. While this is crucial for social functioning, findings on social-cognitive abilities in patients with MUS, such as to recognize others’ emotions and mental states, and to empathize with others, are heterogeneous. The aim of this dissertation was to improve the understanding of emotion processing in patients with MUS, to shed light on potential maintaining factors and to provide suggestions on the improvement of existing psychotherapeutic interventions. Applying an experimental emotion recognition task and a trust game, as well as assessing self-reported emotional awareness, an intact perception of others’ emotions despite deficits in understanding own feelings were revealed in patients with somatic symptom disorder compared to healthy controls. Furthermore, the findings indicated a lack of trust and a negative perception of others. Regarding emotion regulation, a self-reported higher level of habitual use of expressive suppression was revealed. Further, emotion recognition and the attribution of mental states to others were investigated experimentally in patients with hypochondriasis compared to a depressive and a healthy control group. Here again, the findings indicate intact mentalizing abilities. Moreover, own reactions to others’ emotions were assessed using a self-report questionnaire and point to higher levels of personal distress in health anxiety in comparison to both other groups. In addition, patients with hypochondriasis reported more empathic concern than healthy controls. The findings of this thesis confirm the assumptions that patients with MUS suffer from emotion dysregulation, since they exhibit high levels of alexithymia and show more habitual use of expressive suppression in order to cope with feelings, which is considered to be rather maladaptive and to further enhance physiological aspects of emotional arousal. Nevertheless, an intact perception of others’ emotions and mental states was demonstrated. However, the presented results point to problematic reactions to others’ aversive emotions, reflected by high levels of personal distress. In conclusion, the results indicate the importance of raising emotional awareness and improving emotion regulation in patients with MUS.